Ripplocations: A Progress Report - Barsoum, Michel W. (Frontiers in Materials, 2020)
It has long been recognized that when the basal planes of crystalline layered solids were loaded in compression edge-on they failed by the formation of kink bands. And while no good model was ever put forth for how that occurred, it was always implicitly, or explicitly, assumed that basal dislocations, BDs, were the culprit. In 2015, the term ripplocation – best described as an atomic layer ripple - was coined and since then we have been making the case that atomic layers, like in other layered systems – be they playing cards, steel sheets or geological formations – also fail by constrained buckling. In graphite, beyond a critical buckling stress, ripplocation boundaries, RB, whose width is equal to the width of the perturbing load are formed. RBs - precursors of kink boundaries, KBs, and fully recoverable - are defined as the locus of points with the highest curvature in each layer. Once nucleated the RBs very rapidly indeed propagate, wave-like, away from under the perturbation. Once they reach a boundary standing waves, whose crests are RB, are formed. It is the to-and-fro motion of such waves and the concomitant friction between the layers that is responsible for the energy dissipated per cycle per unit volume outlined by stress-strain loops characteristic of layered solids that are cyclically loaded. The driving force for the reversibility of these loops is the elastic energy stored in the RBs and matrix surrounding them. Constraining motion normal to the basal planes results in an increase in buckling stresses and a decrease in the wavelengths of the resulting waves. The results of a folding mechanics model, based on confined buckling – that takes into account frictional, bending and foundation energies – on thin steel sheets not only agree surprisingly well with our experimental results, especially at low confining pressures, but also with previous work. At the atomic level transmission electron microscope, TEM, images on the MAX phases, graphite and a layered silicate all confirm existence of ripplocations.. The existence of bulk ripplocations will require a revisiting and reassessment of our understanding of how layered crystalline solids deform.